Material selection for ornamental products based on carbon footprint and embodied water - Mudgal, Devanshu; Pagone, Emanuele; Salonitis, Konstantinos (Springer, 2022)
This paper analyses and compares the Life Cycle Assessment of ceramics, bricks, steel, clay, and polypropylene with cast stone widely used in architectural ornaments. Architectural ornaments include, for example, statues, Georgian architectural window surrounds and balustrading etc. A methodology was proposed within this study which was verified after being applied to the case study. The Life Cycle Assessment of all the materials was performed from “cradle-to-gate” for a kilogram of each material. The transportation of the finished goods is also included in this study as that is a crucial part of a business. The selected materials were compared based on the overall carbon dioxide equivalent, water, and energy consumption during the general manufacturing process. Materials were plotted at the end of this study based on each parameter. Concrete showed the lowest contribution towards the carbon dioxide equivalent whereas cast stone had the lowest water consumption. Polypropylene had the highest energy consumption. A few recommendations to make cast stone greener were also made at the end of this paper.
Keywords: Cast stone; life cycle analysis; carbon footprint; embodied water